2006
DOI: 10.1177/875697280603700307
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Analysis of Project Management Maturity

Abstract: This paper examines and identifies core dimensions of assessment frameworks, including five core requirements for conducting assessments, two key processes of assessing organizations (audit and self-assessment), and two dimensions of improving performance (delivering data and applying data). It discusses the evolution of using maturity models to assess organizational capabilities and the development of maturity models to assess project management competencies. It then outlines a five-level project management m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
62
0
9

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(86 citation statements)
references
References 13 publications
3
62
0
9
Order By: Relevance
“…Although certain studies, including research done by Mullaly [38], [40] as discussed in the previous paragraph, failed to prove that high maturity in project management correlates with better results [9]. Dooley et al [41] disagreed, finding that higher levels of maturity were associated with projects that met organisational goals such as cost goalsi.e., projects that perform well.…”
Section: Figure 3: Project Management Maturity Model (Pm 3 ) [31]mentioning
confidence: 94%
See 2 more Smart Citations
“…Although certain studies, including research done by Mullaly [38], [40] as discussed in the previous paragraph, failed to prove that high maturity in project management correlates with better results [9]. Dooley et al [41] disagreed, finding that higher levels of maturity were associated with projects that met organisational goals such as cost goalsi.e., projects that perform well.…”
Section: Figure 3: Project Management Maturity Model (Pm 3 ) [31]mentioning
confidence: 94%
“…Skulmosky [39] suggests, but does not demonstrate, that there is a link between project management maturity and competency. Recent longitudinal studies of organisational maturity have also been unable to prove a clear link between project management maturity and performance [38], [40]. Mullaly [38] further suggests that project management maturity models need to change their focus from just process maturity to a broader cognisance of organisational maturity.…”
Section: Figure 3: Project Management Maturity Model (Pm 3 ) [31]mentioning
confidence: 99%
See 1 more Smart Citation
“…A stream of research claims that they lack foundations (Cooke-Davies, 2007;Jugdev & Thomas, 2002;Mullaly, 2006), there is a lack of agreement among researchers on what comprises the project management maturity construct Pasian et al, 2012) and a lack of evidence of the relationship of maturity and perceived outcomes (Ahlemann et al, 2009;Besner & Hobbs, 2008a;Killen & Hunt 2013;Mullaly, 2014).…”
Section: Main Criticisms and Insightsmentioning
confidence: 99%
“…While embracing risk management, the implementation struggle seems to remain (Oversight Systems, 2006). 15 A longitudinal project management analysis over the years 1998-2003, which was initiated by the Project Management Institute (PMI), showed that organizations consistently fail to apply risk management across projects (Mullaly, 2006). Researchers and practitioners, such as Hillson (2002), Hillson and Murray-Webster (2007), and Olsson (2006) confi rm these 12 On November 1, 2007, leading organizations in the Dutch construction industry signed an agreement on the rigorous application of risk management within Dutch construction projects.…”
mentioning
confidence: 99%